2003
DOI: 10.1210/en.2003-0502
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Vitamin D Receptor Gene in Mice Results in Abnormal Skeletal Muscle Development with Deregulated Expression of Myoregulatory Transcription Factors

Abstract: Although rachitic/osteomalacic myopathy caused by impaired vitamin D actions has long been described, the molecular pathogenesis remains elusive. To determine physiological roles of vitamin D actions through vitamin D receptor (VDR) in skeletal muscle development, we examined skeletal muscle in VDR gene deleted (VDR -/-) mice, an animal model of vitamin D-dependent rickets type II, for morphological changes and expression of myoregulatory transcription factors and myosin heavy chain isoforms. We found that eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
339
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(366 citation statements)
references
References 36 publications
22
339
0
5
Order By: Relevance
“…(40) Mice lacking the VDR show a skeletal muscle phenotype with smaller and variable muscle fibers and persistence of immature muscle gene expression during adult life. (34,41) Second, proximal muscle weakness is a prominent feature of the clinical syndrome of vitamin D deficiency. (42) Clinical findings in vitamin D deficiency myopathy include proximal muscle weakness, diffuse muscle pain, and gait impairments such as waddling way of walking.…”
Section: Discussionmentioning
confidence: 99%
“…(40) Mice lacking the VDR show a skeletal muscle phenotype with smaller and variable muscle fibers and persistence of immature muscle gene expression during adult life. (34,41) Second, proximal muscle weakness is a prominent feature of the clinical syndrome of vitamin D deficiency. (42) Clinical findings in vitamin D deficiency myopathy include proximal muscle weakness, diffuse muscle pain, and gait impairments such as waddling way of walking.…”
Section: Discussionmentioning
confidence: 99%
“…This is not completely unexpected since vitamin D plays essential roles in regulating muscle contractility [7] and muscle growth [6]. Renal failure results in abnormalities in vitamin D metabolism due to the decline in proximal tubular production of 1α-hydroxylase.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D plays an essential role in muscle growth and development [6] and in regulating muscle contractility [7]. Numerous studies in animals and humans have demonstrated the effects of vitamin D deficiency on various aspects of muscle cell function [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…В немногих экспериментальных исследованиях также показано значение РВД для респираторной системы: у мышей с отсутствием РВД авторы наблюдали раннее разви-тие ХОБЛ и эмфиземы, хронического воспаления и иммунной дисрегуляции, легочной деструкции, снижение в легких инфильтрации лимфоцитами и эозинофилами; однако при увеличении цитокинов и IgE наблюдали отсутствие гиперреактивного отве-та, в то же время терапия витамином D у этих мышей не влияла на течение у них БА [36]. Также показа-но влияние отсутствия РВД у мышей на редукцию в 20 % всех миофибрилл и нарушение в них регуля-торной mrf с ограничением роста и дифференциации миоцитов [37].…”
Section: Introductionunclassified